Secular Trends of the Impact of Overweight and Obesity on Hypertension in Yi People: Yi Migrant Study, 1996–2015 - Jia Zhang; Shaoping Wan; Fen Dong; Li Pan; Wuli Yihuo; Haiying Gong; Fang Yang; Zheng Li; Guoju Li; Xiaoyang Wang; Guangliang Shan (International Journal of Hypertension)
Background. Rising hypertension prevalence, coupled with increasing overweight and obesity rates, has been observed in Yi people. Moreover, the growing blood pressure level among Yi people was mostly attributable to the continuous increase of body mass index (BMI). However, little is known about the trend of association between them. Methods. Consequently, we investigated the impact of overweight/obesity on hypertension over three periods (1996, 2007-2008, 2015) using data from Yi Migrant Study (n = 8749). The Yi Migrant Study incorporated three successive cross-sectional studies which were implemented by the same team with consistent protocols. Results. Compared with period 1 (1996), the influence of overweight/obesity on hypertension risk significantly increased in period 2 (2007-2008) and period 3 (2015); relative excess risk due to interaction (RERI) was 1.59 (95% CI: 0.12, 3.05) and 1.41 (95% CI: 0.30, 2.78), respectively. Meanwhile, the overweight/obese population in period 3 did not show hypertension risk higher than that in period 2 (RERI = 0.15; 95% CI: −0.76, 1.07). Additionally, we observed a continuously growing trend of hypertension risk among normal weight Yi people. Conclusions. During the past two decades, there was a significant increase in the association between overweight/obesity and hypertension in Yi people, whereas the increasing trend has leveled off in more recent years. These findings suggest that overweight/obesity and hypertension are becoming more epidemic comorbidity over time. Interventions to prevent hypertension should focus not only on the overweight/obese population, but also on those with normal weight.